2018
DOI: 10.1016/j.jaridenv.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Albedo estimated from remote sensing correlates with ecosystem multifunctionality in global drylands

Abstract: Monitoring ecosystem functioning is a significant step towards detecting changes in ecosystem attributes that could be linked to land degradation and desertification in drylands worldwide. Remote sensing-based vegetation indices (VIs) and land surface albedo are two favorite indicators to monitor desertification process due to their close relationship with ecosystem status and to their increasing applicability over multiple spatiotemporal scales. While VIs are routinely used to monitor ecosystem attributes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
2
23
0
1
Order By: Relevance
“…Temperatures (LST) ranged from −25 • C to 45 • C. (3) Albedo (ALB; MCD43A3.006). ALB is surrogate for surface properties such as the extent and nature of the vegetation cover, and it is affected by the change of the land-surface bio-physical factors such as vegetation, LST and soil moisture [35]. ALB values ranged from 0 to 1 (fresh snow and bare soil usually fall around 0.9).…”
Section: Satellite-derived Products and Efasmentioning
confidence: 99%
“…Temperatures (LST) ranged from −25 • C to 45 • C. (3) Albedo (ALB; MCD43A3.006). ALB is surrogate for surface properties such as the extent and nature of the vegetation cover, and it is affected by the change of the land-surface bio-physical factors such as vegetation, LST and soil moisture [35]. ALB values ranged from 0 to 1 (fresh snow and bare soil usually fall around 0.9).…”
Section: Satellite-derived Products and Efasmentioning
confidence: 99%
“…2). SA exhibited a greater sensitivity to changes involving characteristics other than the greenness of leaves because this index covers other bands (SWIR 1 and SWIR 2) of the electromagnetic spectrum (Lui et al, 2017;Zhao et al, 2018), which are not used by indices that use VIS-NIR. When a soil-plant-atmosphere system is altered by an action of deforestation, the leafless woody biomass, which represents ca.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of LCC in seasonally dry forests by using VIS-NIR, such as EVI and NDVI, is limited due to difficulties distinguishing deciduous vegetation from the underlying ground during the dry period (Daughtry, 2001;Jacques et al, 2014;Mayes et al, 2015;Nagler et al, 2000;Xu et al, 2014). Zhao et al (2018) highlight that while vegetation indices are routinely used to monitor ecosystem attributes and functions such as vegetation cover and primary productivity, the remote sensing-measured surface albedo (SA) can be used to assess ecosystem status in drylands. SA is more sensitive to changes in biomass (Rodríguez-Caballero et al, 2015); it has been used to monitor changes in dryland ecosystems, and it is positively correlated with exposed soils (Yu et al, 2017), which are the outcome of the LCC process (Lamchin et al, 2016;Liu et al, 2016;;Karnieli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the white‐sky albedo (WSA) is related purely to the properties of the land surface and is not affected by atmospheric conditions (Strahler et al, ). Zhao et al () have reported that WSA correlates with ecosystem multifunctionality, which has been found to exhibit two states and abrupt and discontinuous changes along aridity gradients in global drylands (Berdugo, Kéfi, et al, ). WSA (bihemispherical reflectance) is defined as albedo under the condition that the direct component is absent and the diffuse component is isotropic and thus is independent of solar zenith angle.…”
Section: Methodsmentioning
confidence: 99%